The Detection and Reactivity of Silanols and Silanes Using Hyperpolarized 29Si Nuclear Magnetic Resonance. (9th January 2020) - Rayner, Peter J.; Richardson, Peter M.; Duckett, Simon B.
Abstract: Silanols and silanes are key precursors and intermediates for the synthesis of silicon‐based materials. While their characterization and quantification by 29 Si NMR spectroscopy has received significant attention, it is a technique that is limited by the low natural abundance of 29 Si and its low sensitivity. Here, we describe a method using p‐H2 to hyperpolarize 29 Si. The observed signal enhancements, approaching 3000‐fold at 11.7 T, would take many days of measurement for comparable results under Boltzmann conditions. The resulting signals were exploited to monitor the rapid reaction of tris( tert ‐butoxy)silanol with triflic anhydride in a T 1 ‐corrected process that allows for rapid quantification. These results demonstrate a novel route to quantify dynamic processes and intermediates in the synthesis of silicon materials. Abstract : Silanole und Silane wurden mit Parawasserstoff und einem Iridium‐Katalysator hyperpolarisiert. Die erzielten 29 Si‐NMR‐Signalgewinne erreichten einen Faktor von fast 3000 und wurden für die quantitative Nachverfolgung einer Substitutionsreaktion verwendet.